2014
DOI: 10.1590/s1679-45082014rw2591
|View full text |Cite
|
Sign up to set email alerts
|

Scales on Quality of Life in patients with spinal cord injury: integrative review

Abstract: Studies evaluating the Quality of Life of individuals with spinal cord injury using different research tools demonstrate that the Quality of Life scores are considered low both in national and international studies. The objective of this review was to characterize the international scientific production about the most used scales to assess Quality of Life in patients with spinal cord injury. We examined articles on Quality of Life of patients with spinal cord injury published over the last 5 years and indexed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
(13 reference statements)
0
7
0
2
Order By: Relevance
“…Several reviews have summarised both the utilisation and validity of QoL tools for SCI and LLA populations [2731, 48, 54, 55]. These indicate that the WHOQOL-BREF [56] and Medical Outcomes SF-36 [57] are in common use and considered amongst the best available generic tools for both groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reviews have summarised both the utilisation and validity of QoL tools for SCI and LLA populations [2731, 48, 54, 55]. These indicate that the WHOQOL-BREF [56] and Medical Outcomes SF-36 [57] are in common use and considered amongst the best available generic tools for both groups.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers in both LLA and SCI communities acknowledge the value of QoL measures as longitudinal assessment tools [17, 2731]. They provide a quantitative mechanism for capturing changes in post-injury health and broad level treatment outcomes, both for an individual and for a disability group, relative to population normative data.…”
Section: Introductionmentioning
confidence: 99%
“…A chaptalização, foi realizada de acordo com Aquarone et al (2001) no qual adicionou-se 17 g de açúcar por litro para aumentar 1 ºGL. Esse cálculo é valido quando a vinificação é efetuada a baixa temperatura, entretanto, numa vinificação em tinto geralmente a temperatura é mais elevada, ocasionando desta forma um rendimento menor.…”
Section: Methodsunclassified
“…The test comprises 36 items, divided into 8 subscales that evaluate the following areas: physical function (10 items), role limitations due to physical issues (4 items), pain (2 items), general health appreciation (5 items), vitality (4 items), social function (2 items), role limitations due to emotional issues (3 items), mental health (5 items), and an additional item that compares actual health with previous year perception of health [16]. Many studies have found with this instrument that SCI has a negative influence on the quality of life of patients [17].…”
Section: Sf-36mentioning
confidence: 99%